L’évolution de l’affirmative action aux États-Unis sous la présidence de George W. Bush - Marie-Christine Pauwels (Revue LISA)
This article examines the fate of affirmative action in the United States during the eight years of the Bush administration. After a brief reminder of the major landmarks which have curbed and narrowed affirmative action over the past twenty years and seen its legitimacy questioned, a new perspective will be given on the backlash many of these programs are currently experiencing. While many affirmative action measures have indeed been scaled back since the Reagan years, new, innovative strategies are emerging today to protect equal opportunity in public contracting, education and employment. These strategies are based on playing down race and ethnicity, enhancing instead more neutral criteria such as geography and residence. In education, for example, several states have adopted “percentage plans”, which call for colleges and universities to admit the top students of each high school class, regardless of their race or ethnicity. On flagship campuses, admissions policies which indirectly target under-represented minority groups have been imagined. And similar roundabout policies in which race is implicitly targeted yet never mentioned as such have been increasing in the field of public contracting. The SBA HUBZone program that promotes economic development in distressed neighborhoods by providing access to more federal contracting opportunities is a good example. These transformations are also interesting to analyse from a transnational perspective and a comparison with the French model of affirmative action, which is both geographically-targeted and geared toward playing down the visibility of race and ethnicity, will be made.